Analisa Kualitatif Tentang Strategi Guru Dalam Mengatasi Kesulitan Siswa Dalam Memahami Materi Pendidikan Agama Islam Di SMPN 1 Medan - Ramadhan, Surya; Lubis, Abdul Habib; Putri, Ridha Hasanah (EL-EMIR Institute, 2025)
This study aims to analyze in depth the strategies implemented by teachers in overcoming students' difficulties in understanding Islamic Religious Education (PAI) materials. This study uses a qualitative approach with a descriptive method, where data is collected through direct observation in class, in-depth interviews with teachers and students, and documentation studies of learning devices and student evaluation results. The subjects of the study consisted of PAI teachers and students in grades VII and VIII at a state junior high school. The results of the study showed that teachers face various challenges, such as low student motivation to learn, minimal background understanding of religion from the family environment, and student dependence on memorization methods. To overcome this, teachers apply several strategies, including: (1) the use of contextual approaches that link religious material to students' daily lives; (2) the use of visual and audio media to attract students' interest; (3) the application of active learning methods such as group discussions, case studies, and role-playing; (4) providing individual guidance to students who experience special difficulties; and (5) strengthening character and spiritual values ​​through school religious activities. These strategies are considered quite effective in helping students improve their understanding of Islamic Religious Education concepts that were previously difficult for them to understand. However, the results of the study also show that the success of the strategy is greatly influenced by external factors, such as parental support, learning environment conditions, and the availability of learning support facilities. This study recommends the need for ongoing training for Islamic Religious Education teachers in developing innovative learning methods and collaboration between schools, parents, and the community in supporting more effective Islamic religious education.